PTU-037 Predicting inflammatory pathology at capsule enteroscopy: what is the utility of a raised faecal calprotectin?. (22nd June 2015) - Parker, C; Lamb, CA; Robinson, M; Mansfield, JC; Gunn, M
Abstract : Introduction: Faecal Calprotectin (FCP) is a widely used biomarker of gastrointestinal (GI) mucosal inflammation. Many capsule enteroscopy (CE) services are receiving increased referrals of patients with abdominal symptoms combined with an elevated FCP (>50 µg/g) but normal gastroscopy, colonoscopy or radiology. There is little data on using FCP levels as a screening tool for selecting patients in whom CE will lead to a definitive diagnosis. Elevated FCP levels may indiscriminately drive investigations in endoscopy and imaging-negative patients who subsequently have normal findings at CE. We aimed to determine the incidence of inflammatory pathology on CE in patients with a raised FCP, and if a suitable concentration of the biomarker could be identified as a screening tool to avoid unnecessary CE. Method: A single centre retrospective review of The Newcastle upon Tyne Hospitals CE database was conducted (Feb 2012–Feb 2015). Patients with GI symptoms (abdominal pain, diarrhoea, bloating, vomiting, weight loss) and a raised FCP (>50 µg/g) were identified. Findings at CE considered to be inflammatory were: erythema, ulceration, erosions and fissuring. Results: 35 patients were identified with elevated FCP and GI symptoms. 45.7% (n = 16) had inflammation identified by CE and in 54.3% (n = 19) no inflammatory pathology was identified. The mean (+/-SE) FCP was higher in patients with evidence of inflammation at CE in comparison to those with no inflammation: 452.1 (95.8) µg/g vs. 206 (20.8) µg/g; p = 0.01. Stratifying patients according to FCP revealed that only 8.3% of patients (n = 1/12) with a FCP of 50–200 µg/g had inflammatory findings at CE. This rose to 58.3% of patients (n = 7/12) with a FCP of 201–300 µg/g, and 72.7% of patients (n = 8/11) with a FCP >300 µg/g. A threshold of 200 µg/g FCP revealed a sensitivity of 94.1% to predict inflammation at CE, with a specificity of 55.6%. This FCP threshold had a negative predictive value of 90.9%, and positive predictive value of 66.7% for CE inflammation. Conclusion: In this small retrospective analysis of a sub-group of patients referred for CE with a FCP of >50 μg/g the likelihood of identifying inflammatory pathology at CE increased with rising FCP concentrations above 200 μg/g. A threshold of 200 μg/g provided a high negative predictive value for CE inflammation and may be a useful screening tool to reduce the requirement for CE in select patient groups. This retrospective analysis should be confirmed in a larger prospective cohort. Disclosure of interest: None Declared.